Simulated driving behavior over the adult age span - Felix Menze; Felix Menze; Nathan W. Churchill; Nathan W. Churchill; Nathan W. Churchill; Tom A. Schweizer; Tom A. Schweizer; Tom A. Schweizer; Simon J. Graham; Simon J. Graham (Frontiers in Aging Neuroscience)
BackgroundMotor vehicle accidents remain a leading cause of accidental death worldwide. Death and injury rates are particularly high for both young inexperienced drivers and elderly drivers. Understanding the behavioral changes that are associated with maturation and aging could inform assessments of driving performance and lead to new measures identifying at-risk drivers. To shed further light on such effects, this study aims to characterize simulated driving behavior across and within age groups using a large driving simulation dataset.MethodsThe analyzed dataset consisted of 112 participants [47/112 (42%) female] between the ages of 17 and 85 (average ± standard deviation: 54 ± 22 years). Participants performed navigation in scenarios modeled after the standard licensing test of Ontario, Canada, which included a series of turns at intersections with different levels of complexity (e.g., involving oncoming traffic or pedestrians) and levels of distraction (requiring auditory responses to common-knowledge questions). Behavioral metrics were defined and investigated not only for the full completion of each task but also based on common subtasks (e.g., braking at an intersection), which were then compared across and within age groups (young, middle-aged, old).ResultsOverall, young adults behaved similarly to middle-aged adults for basic tasks but showed differences during traffic navigation subtasks when distracted, such as starting to decelerate significantly later when approaching intersections. Old drivers, on the other hand, drove at lower average speed, stopped earlier at intersections, and left increased distances to pedestrians, but required significantly more time to complete the driving tasks.ConclusionWith rich detail arising from intra-task quantification, the results were consistent with and additive to previous literature showcasing that compared to middle-aged adults, young adults showed performance suggestive of riskier driving behavior, and old adults showed performance suggestive of caution consequent to declining driving ability. In particular, the intra-task quantification revealed that the driving of young adults was more impacted by the presence of distraction (e.g., delayed decelerating), whereas old adults prioritized safe driving (e.g., correctly braking at intersections) over responding to distractions. The study may be used as motivation for future studies of driving safety and accident prevention, and informed assessment of governmental regulations.